Overview of Pneumonia Treatment in Hospitalized Geriatric Patients at One of the Gorontalo Provincial Hospitals: Case Report - Papeo, ⁠Dizky Ramadani Putri; Kai, Mohamad Nur Fadjri; Isa, Moh. Arya Avrilio; Sumaga, Nabila Natasya; Mursidi, Sitti Rahmawaty Sisilia; Canon, Afifah Aliya (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
Pneumonia is a common respiratory infection affecting all age groups, particularly the elderly, who are more susceptible due to comorbidities and age-related decline in immune function. This case report aims to evaluate the role of clinical pharmacy in the management of community-acquired pneumonia (CAP) in a geriatric patient. A descriptive qualitative method was conducted through retrospective analysis of medical records, including clinical presentation, diagnostic findings, pharmacological and non-pharmacological interventions, and patient outcomes. The pharmacological therapy included ceftriaxone and azithromycin as antibiotics, mucolytics, bronchodilators, antipyretics, gastrointestinal protection, and vitamin supplementation, with clinical pharmacy involvement in therapy optimization and monitoring. Non-pharmacological strategies involved oxygen therapy, semi-Fowler positioning, effective coughing techniques, and hydration support. The patient showed marked clinical improvement with increased SpO₂ from 95% to 98%, a reduction in respiratory rate from 30 to 22 breaths/minute, and symptom resolution by day four. This report highlights that the integration of clinical pharmacy interventions significantly contributes to effective and safer management of CAP in elderly patients